Digital Transformation of Islamic Media (Descriptive Analysis of Republika Transition to Full-Digital in 2023) - Soewardi, Euis Evi Puspitasari; Roni Tabroni; Arief Permadi (Jogjakarta Communication Conference (JCC), 2023)
Digitalization of media in Indonesia is now a trend, both locally and nationally. Like Republika, which has undergone a digital transformation by fully switching to a digital platform at the beginning of 2023, as a response to the development of information technology. This research aims to explain the reasons, commitment, and prospects of Republika after the print version ended. This study uses descriptive analysis with sources from policy makers in Republika, who have expressed their opinions through the Republika newspaper a week before the print version ended. The findings in this study are the readiness of Republika to fully transform to a digital platform. The added value obtained by Republika is unlimited space and a wider reach. Meanwhile, Republika assurance is to maintain the quality of content, maintain good journalism traditions, and maintain Republic's inclusive Islamic ideology in Indonesia.